Sensitivity of MG‐ADL for generalized weakness in myasthenia gravis. (17th December 2018) - de Meel, R. H. P.; Raadsheer, W. F.; van Zwet, E. W.; Verschuuren, J. J. G. M.; Tannemaat, M. R.
Abstract : Background and purpose: Myasthenia gravis activities of daily living (MG‐ADL) is a commonly used questionnaire in MG trials. To investigate whether MG‐ADL is equally sensitive to oculobulbar and generalized weakness, its correlation with the oculobulbar and generalized domain of the quantitative myasthenia gravis (QMG) score was analyzed (QMGob and QMGgen, respectively). To test whether the sensitivity of MG‐ADL for generalized weakness could be improved, the additional value of ACTIVLIM on top of MG‐ADL in the prediction QMGgen in was investigated. Methods: MG‐ADL, QMG and ACTIVLIM, an ADL questionnaire focusing on generalized weakness, were analyzed in a prospective cohort of 112 MG patients. A generalized linear model was used to calculate the correlation of MG‐ADL with QMGob and QMGgen and to assess the additional value of ACTIVLIM on top of MG‐ADL for its correlation with QMGgen. Results: MG‐ADL had a higher correlation with QMGob than with QMGgen ( B = 0.68, P < 0.001, and B = 0.38, P < 0.001, respectively). A similar trend was found for changes in the scores ( B = 0.68, P = 0.132, and B = 0.39, P = 0.492, respectively). ACTIVLIM had a significant additional value on top of MG‐ADL in the prediction of QMGgen, both cross‐sectionally ( B = −0.61, P < 0.001) and for changes within individual patients ( B = −0.93, P = 0.041). Conclusion: MG‐ADL has a lower sensitivity for generalized weakness than for oculobulbar weakness. Adding questions on generalized weakness would improve the sensitivity of the MG‐ADL for generalized weakness.